A review of the costs of delivering maternal immunisation during pregnancy. Issue 40 (11th September 2020) - Procter, Simon R; Salman, Omar; Pecenka, Clint; Gonçalves, Bronner P; Paul, Proma; Hutubessy, Raymond; Lambach, Philipp; Lawn, Joy E; Jit, Mark
Abstract: Background: Routine maternal immunisation against influenza and pertussis are recommended by the WHO to protect mother and child, and new vaccines are under development. Introducing maternal vaccines into national programmes requires an understanding of vaccine delivery costs – particularly in low resource settings. Methods: We searched Medline, Embase, Econlit, and Global Health for studies reporting costs of delivering vaccination during pregnancy but excluded studies that did not separate the vaccine purchase price. Extracted costs were inflated and converted to 2018 US dollars. Results: Sixteen studies were included, of which two used primary data to estimate vaccine delivery costs. Costs per dose ranged from $0.55 to $0.64 in low-income countries, from $1.25 to $6.55 for middle-income countries, and from $5.76 to $39.87 in high-income countries. Conclusions: More research is needed on the costs of delivering maternal immunisation during pregnancy, and of integrating vaccine delivery into existing programmes of antenatal care especially in low and middle-income countries.